2016
DOI: 10.1016/j.ophtha.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 Study of Intravitreous E10030 in Combination with Ranibizumab in Neovascular Age-Related Macular Degeneration

Abstract: Intravitreal E10030 administered at doses up to 3 mg in combination with ranibizumab was well tolerated without evidence of systemic or ocular toxicity in participants with NVAMD. The changes in both mean VA and imaging biomarkers suggest a favorable short-term safety profile for the combination therapy of E10030 and ranibizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…There are several alternative antiangiogenic ocular drugs under development. Fovista (E10030; Ophthotech, New York, NY), 36 CrossMAb (RG7716; Roche, Basel, Switzerland), 28 Conbercept (KH902; Chengdu Kanghong Biotech Co, Ltd, Sichuan, China), 37 Pazopanib (GW786034; GlaxoSmithKline, Research Triangle Park, NC), 38 AdPEDF (GenVec, Inc, Gaithersburg, MD), 39 and many others are showing interesting outcomes. In the future, we likely will have a combination of angiogenesis inhibitors, or a more effective one, that concurrently addresses various vasogenic mediators and pathways.…”
Section: Discussionmentioning
confidence: 99%
“…There are several alternative antiangiogenic ocular drugs under development. Fovista (E10030; Ophthotech, New York, NY), 36 CrossMAb (RG7716; Roche, Basel, Switzerland), 28 Conbercept (KH902; Chengdu Kanghong Biotech Co, Ltd, Sichuan, China), 37 Pazopanib (GW786034; GlaxoSmithKline, Research Triangle Park, NC), 38 AdPEDF (GenVec, Inc, Gaithersburg, MD), 39 and many others are showing interesting outcomes. In the future, we likely will have a combination of angiogenesis inhibitors, or a more effective one, that concurrently addresses various vasogenic mediators and pathways.…”
Section: Discussionmentioning
confidence: 99%
“…AXT107 also reduces ligand-induced phosphorylation of c-Met and PDGFRβ, which may also contribute. Combined neutralization of VEGF and PDGF-BB results in significantly greater suppression of murine choroidal NV and regression of choroidal NV with superior vision outcomes in patients with NVAMD than suppression of VEGF alone ( 4547 ). Because AXT107 inhibits both VEGFR2 and PDGFRβ signaling and causes regression of choroidal NV, similar superior outcomes in NVAMD as those seen with combination therapy might be expected with injection of a single small peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, preliminary data from ongoing clinical trials have been reported to show beneficial additive effects of fovista treatment in combination with antieVEGF-A therapies in patients with neovascular AMD. 12,15 …”
Section: Discussionmentioning
confidence: 99%